Comparison of in-hospital outcomes and long-term survival for valve-in-valve transcatheter aortic valve replacement versus the benchmark native valve transcatheter aortic valve replacement procedure - Matta, Anthony; Levai, Laszlo; Roncalli, Jerome; Elbaz, Meyer; Bouisset, Frederic; Nader, Vanessa; Blanco, Stephanie; Campelo Parada, Francisco; Carrié, Didier; Lhermusier, Thibault (Frontiers in Cardiovascular Medicine, 2023)
Background In recent years, the number of patients with failed surgically implanted aortic bioprostheses and the number of candidates for valve-in-valve transcatheter aortic valve replacement (VIV-TAVR) have been increasing. Objectives The purpose of this study is to evaluate the efficacy, safety, and long-term survival outcomes of VIV-TAVR compared with the benchmark native valve transcatheter aortic valve replacement (NV-TAVR). Methods A cohort study was conducted on patients who underwent TAVR in the department of cardiology at Toulouse University Hospital, Rangueil, France between January 2016 and January 2020. The study population was divided into two groups: NV-TAVR (N = 1589) and VIV-TAVR (N = 69). Baseline characteristics, procedural data, in-hospital outcomes, and long-term survival outcomes were observed. Results In comparison with NV-TAVR, there are no differences in TAVR success rate (98.6 vs. 98.8%, p = 1), per-TAVR complications (p = 0.473), and length of hospital stay (7.5 ± 50.7 vs. 4.4 ± 2.8, p = 0.612). The prevalence of in-hospital adverse outcomes did not differ among study groups, including acute heart failure (1.4 vs. 1.1%), acute kidney injury (2.6, 1.4%), stroke (0 vs. 1.8%, p = 0.630), vascular complications (p = 0.307), bleeding events (0.617), and death (1.4 vs. 2.6%). VIV-TAVR was associated with a higher residual aortic gradient [OR = 1.139, 95%CI (1.097–1.182), p = 0.001] and a lower requirement for permanent pacemaker implantation [OR = 0.235 95%CI (0.056–0.990), p = 0.048]. Over a mean follow-up period of 3.44 ± 1.67 years, no significant difference in survival outcomes has been observed (p = 0.074). Conclusion VIV-TAVR shares the safety and efficacy profile of NV-TAVR. It also represents a better early outcome but a higher non-significant long-term mortality rate.